Book Review: Learning with the labyrinth: creating reflective space in higher education, edited by Jan Sellers and Bernard Moss - Alison James (Association for Learning Development in Higher Education (ALDinHE), 2016)
This book discusses the theory and practice of labyrinth creation and use. From issues of design and cost, to how a labyrinth may be used as a university-wide resource and also be used for outreach to the wider community, it covers labyrinth use: Within disciplines, such as initiatives to deepen reflection and explore contemplative approaches to learning In wider university contexts, such as counselling; chaplaincy; learning and educational development; widening participation and student transition Across the whole university, and reaching out to the wider community of which the university is a part, from the labyrinth as a conference resource (as well as topic), to festival contributions. Learning with the Labyrinth seeks to illustrate, inspire and share ideas that can be taken further by the reader.